Jordanian Judicial Oversight of the Arbitration Decision - Al-Sarhi, Mahmoud Nazmi; Al-Alaween, Kamal Abdelrahim (Dirasat: Shari’a and Law Sciences, 2024)
Objectives: This study aims to elucidate the nature and limits of Jordanian judicial control over arbitration decisions and to determine the reasons for filing annulment for arbitration awards through reviewing the Jordanian Arbitration Law, court judgments, the UNCITRAL Arbitration Rules, and the New York Convention relating to foreign arbitration awards and their enforcement. Methods: The study relied on the analytical descriptive approach by extrapolating and analyzing the provisions of the Jordanian Arbitration Law, the Jordanian Civil Procedure Code and some international agreements related to arbitration and reviewing court rulings in Jordan as judicial applications related to the causes of the arbitration decision invalidity case and the implementation of the arbitration decision. Results: The study concludes that the Jordanian judicial control over arbitration decisions takes the form of the annulment claim based on specific reasons defined by the Jordanian legislator. The principle of the autonomy of the will is respected, considering judicial control over arbitration as both preventive and remedial. National and foreign arbitration awards are enforced by adding the enforcement clause from the competent court. Conclusions: The need to work in the new legislative amendments to amend the provisions related to determining the reasons for control prior and following the issuance of the arbitration decision, especially in the continuity of the court in considering the case if the litigants request to continue the case regardless of the arbitration condition.